Downregulation of eEF1A/EFT3-4 Enhances Dopaminergic Neurodegeneration After 6-OHDA Exposure in C. elegans Model - Chalorak, Pawanrat; Dharmasaroja, Permphan; Meemon, Krai (Frontiers in Neuroscience, 2020)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by the aggregation of α-synuclein protein and selective death of dopaminergic (DA) neurons in the substantia nigra of the midbrain. Although the molecular pathogenesis of PD is not completely understood, a recent study has reported that eukaryotic translation elongation factor 1 alpha (eEF1A) declined in the PD-affected brain. Therefore, the roles of eEF1A1 and eEF1A2 in the prevention of DA neuronal cell death in PD are aimed to be investigated. Herein, by using Caenorhabditis elegans as a PD model, we investigated the role of eft-3/eft-4, the worm homolog of eEF1A1/eEF1A2, on 6-hydroxydopamine (6-OHDA)-induced DA neuron degeneration. Our results demonstrated that the expressions of eft-3 and eft-4 were decreased in the 6-OHDA-induced worms. RNA interference (RNAi) of eft-3 and eft-4 resulted in dramatic exacerbation of DA neurodegeneration induced by 6-OHDA, as well as aggravated the food-sensing behavior, ethanol avoidance, and decreased lifespan when compared with only 6-OHDA-induced worms. Moreover, downregulation of eft-3/4 in 6-OHDA-induced worms suppressed the expression of the anti-apoptotic genes, including PI3K/age-1, PDK-1/pdk-1, mTOR/let-363, and AKT-1,2/akt-1,2, promoting the expression of apoptotic genes such as BH3/egl-1 and Caspase-9/ced-3. Collectively, these findings indicate that eEF1A plays an important role in the 6-OHDA-induced neurodegeneration through the phosphatidylinositol 3-kinase (PI3K)/serine/threonine protein kinase (Akt)/mammalian target of rapamycin (mTOR) pathway and that eEF1A isoforms may be a novel and effective pro-survival factor in protective DA neurons against toxin-induced neuronal death.